2014
DOI: 10.1515/tjj-2013-0041
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of the Loss Coefficients in a Linear Cascade

Abstract: This paper reports results of experimental investigations on a linear cascade of axial compressor blades. Experiments were conducted in an open circuit subsonic wind tunnel of Aerodynamics Research Laboratory of the Iran University of Science and Technology. Different Reynolds numbers based on the blade chord length were examined, ranging from 80,000 to 500,000. Flow incidences were changed between −8 to +8 degrees with 2 degrees intervals. Freestream turbulence intensity was changed between 1.25 to 4 percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
0
0
Order By: Relevance
“…Continuous reduction in the pressure loss can be observed for the smooth case by increasing the Reynolds number. This type of variation has already been observed and reported by the present author 14 . In the low levels of roughness (i.e., TC1 test case), loss variations are similar to the smooth case.…”
Section: Total Pressure Losssupporting
confidence: 89%
“…Continuous reduction in the pressure loss can be observed for the smooth case by increasing the Reynolds number. This type of variation has already been observed and reported by the present author 14 . In the low levels of roughness (i.e., TC1 test case), loss variations are similar to the smooth case.…”
Section: Total Pressure Losssupporting
confidence: 89%
“…This is the major mechanism driving transition in separated flows. This finding is well-documented in the literature; see Gaster (1966), Watmuff (1999), McAuliffe and Yaras (2010), Simoni et al (2012), andTaghavi et al (2014). Lang et al (2004) and Marxen et al (2003) showed that the breakdown of these vortical structures forced transition close to the maximum bubble thickness location.…”
Section: Introductionsupporting
confidence: 68%
“…First, for all but the lowest Reynolds number considered, increasing turbulence intensity from 1.27% to 2.63% increases loss between 32% and 56% (depending on Reynolds number) while further raising it to 4.05% decreases loss between 20% and 47%. Second, at the lowest Reynolds number considered the loss increases monotonically with T u because the separation bubble never reattaches to the blade surface (Taghavi et al (2014)). It can also be seen that this trend is the same for the suction side profile loss in Figure 4(b).…”
Section: Loss Behaviourmentioning
confidence: 97%
See 1 more Smart Citation